Sosialisasi dan Pendampingan Kurikulum Merdeka Guru di Sekolah Dasar - Widdy Sukma Nugraha; Eko Fajar Suryaningrat; Muhammad Nurjamaludin; Risma Nuriyanti; Abdul Hakim (Badranaya: Jurnal Pengabdian kepada Masyarakat, 2023)
This community service activity aims to provide knowledge to teachers in Garut district regarding the current independent curriculum. the participants in this activity were elementary school teachers teaching in the Malangbong sub-district environment. The teacher's initial understanding is obtained by giving a pretest to measure the teacher's initial knowledge about the independent curriculum, then followed by a presentation of material related to the independent curriculum. Then to find out the final understanding is done by giving a posttest to see an increase in teacher knowledge about the independent curriculum. The average post score obtained by the teacher is 58 and the posttest average score is 79 where there is an increase of 0.16%. Community service activities ended with assistance in the preparation of learning implementation plans where teachers were asked to make products in the form of teaching modules that were in accordance with the independent curriculum. Based on the products made by the teachers, it is known that 86.7% of the teachers who took part in the activities were able to make teaching modules properly.